Induction heating method for thermomechanical study of NiTi shape memory alloy wire - Karunakaran, Sivasanghari; Abang Abdul Majid, Dayang Laila (Zhongguo Hangkong Taikong Xuehui, 2025)
Thermo-mechanically responsive shape memory alloys (SMA) with high strain generation have shown remarkable properties particularly, the shape memory effect when use as an actuator. However, in practical applications, it is difficult to characterize the shape memory behaviour due to the complex coupling interaction between load and temperature that resulted in dynamic nonlinear hysteresis. The actuation capability of SMA is depending on the heat control mechanism of SMA. Herein, a comprehensive study is established for Flexinol NiTi wire using induction heating and compared to established data to reveal the feasibility of induction heating for SMA thermomechanical characterization. A precise regulated heat control chamber utilizing inducting heating to control the non-linearities in temperature measurement was used to control the heat transfer mechanism of SMA. Temperature-induced shape memory effect of Flexinol NiTi wire with preloads ranging from 5N to 25N were evaluated in terms of the phase transformation temperatures, thermal hysteresis and the generated strains. With increasing preloads, the phase transformation temperatures and transformation strain also increased, while the thermal hysteresis decreased. The strain-temperature curves during thermal loading at different loads demonstrated a prominent shape memory effect using induction heating. The experimental results signified that induction heating offer a regulated temperature control and faster heating capability, thus become a promising heating technique for SMA thermomechanical characterization.